BENTUK PERUBAHAN MAKNA DALAM BAHASA BUGIS (The Form of Meaning Change in Buginese Language) - Herianah Herianah (Balai Bahasa Sulawesi Selatan, 2014)
Aim of the writing is to describe the form of meaning change in Buginese language. The writing applies descriptive qualitative that describes meaning change in Buginese language by listening, interviewing, and documenting technique. Result of analysis shows that there is meaning change in Buginese language. The changes are: (1) in vernacular to Indonesian language; (2) caused by social change; (3) caused by the exchange of sense response; (4) caused by compound lexeme or word; (5) caused by performance of language user; (6) caused by association; (7) caused by the change of form.